Elementos de economía política clásica en el pensamiento político de Hegel - Rámon, Fernando Huesca (Revista Eletrônica Estudos Hegelianos, 2018)
This article contains an extensive analysis of some aspects of the three classics of political economy, Adam Smith, Jean Baptiste Say, and David Ricardo as a means to contribute, after the efforts of Lukácz, Ilting and Priddat, to the understanding of the depth and width of Hegel’s economical studies and the scope of his assimilation, synthesis and critical incorporation of such objects in his mature work, especially in his lectures on Philosophy of Right.